Heart rate variability while assessing transplanted heart reinnervation - M. Kh. Lepshokova; E. D. Kosmacheva (Инновационная медицина Кубани, 2019)
Key difference of the transplanted heart is its full surgical denervation which causes features of transplanted heart physiology. Eventually a great number of studies appeared and they showed signs of innervation partial restoration and its influence on the subsequent social, physical and psychological rehabilitation of the recipients. In the conducted study we confirmed the fact of the transplanted heart reinnervation on the basis of heart rate variability data, and the defined factors influencing indicators of heart rate variability.